2017
DOI: 10.1111/jonm.12527
|View full text |Cite
|
Sign up to set email alerts
|

Kansas nurse leader residency programme: advancing leader knowledge and skills

Abstract: The next steps include the development of an advanced programme. Residency programmes for new nurse leaders are critical for successful transition into management positions.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
47
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 8 publications
(68 citation statements)
references
References 26 publications
0
47
0
Order By: Relevance
“…All studies identified some level of face‐to‐face delivery within the programmes. It was unexpected to find that few programmes utilized online technologies (Flatekval & Corbo, 2019; Shen et al., 2018). With limited costs and time as a barrier to the development and sustainability of NM development programmes (LaCross et al., 2019; Mularz & Johansen, 2016; Warshawsky et al., 2020; Warshawsky & Cramer, 2019), Web use may address these limitations, and those commonly associated with the current COVID‐19 situation, in future programmes.…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…All studies identified some level of face‐to‐face delivery within the programmes. It was unexpected to find that few programmes utilized online technologies (Flatekval & Corbo, 2019; Shen et al., 2018). With limited costs and time as a barrier to the development and sustainability of NM development programmes (LaCross et al., 2019; Mularz & Johansen, 2016; Warshawsky et al., 2020; Warshawsky & Cramer, 2019), Web use may address these limitations, and those commonly associated with the current COVID‐19 situation, in future programmes.…”
Section: Discussionmentioning
confidence: 99%
“…Curriculum content was structured around the core NM competencies derived by the AONL (LaCross et al., 2019; Mackoff et al., 2017; McGarity et al., 2020; Seabold et al., 2020.) In most instances, these competencies were used to design programme curricula and subsequently evaluate the programme (Flatekval & Corbo, 2019; Kuraoka, 2018; Mackoff et al., 2017; Manning et al., 2015; McGarity et al., 2020; Seabold et al., 2020; Shen et al., 2018).…”
Section: Key Themes From the Literaturementioning
confidence: 99%
See 3 more Smart Citations